A BRIEF REVIEW OF SOURCES ON EMENDATIO MORAE IN THE DIGEST OF JUSTINIAN - Kulauzov, Maša; Milutin, Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Purgatio or emendatio morae would in the literal translation into English mean purging the default. In Roman classical law, it amounted to the possibility of the debtor in default, firstly, to fulfil the primary obligation and, secondly, to remediate potential legal effects of the consequences of mora debitoris. There were other ways of purging the default as well. As a consequence of emendatio morae, debtor’s obligations, both primary and secondary ones, would cease to exist and the consequences of mora debitoris would cease to produce legal effects. Therefore, purgatio morae consisted of two elements: debtor’s offer to completely fulfil the prestation owed as well as his offer to remediate the legal effects of the consequences of the default.
Keywords: debtor’s default purging, purgatio morae, emendatio morae, debtor’s default, mora debitoris, mora solvendi